A reflection on information systems strategizing: the role of power and everyday practices. (17th May 2016) - Marabelli, Marco; Galliers, Robert D.
Abstract: We review the IS strategizing literature and highlight its main strengths and weaknesses. Strengths include an account given to the relevance of tensions between planned and executed strategy, and associated tradeoffs such as rigidity and flexibility, formal and informal strategizing and the exploitation of static resources vis à vis the exploration of novel capabilities. Weaknesses relate to a predominant focus on an organizational level of analysis and a lack of power considerations. In this paper we aim to build on these strengths and to ameliorate these weaknesses by proposing a comprehensive IS strategizing framework that uses extant IS strategizing research as a foundation, rejuvenated by insights from the emerging strategy‐as‐practice literature. The paper extends our understanding of IS strategizing in light of the practice perspective by providing a multilevel account and incorporating power considerations.